"I have seen the custom of the King of Egypt in our time as well." A study in comparative Midrash and commentary - Shemesh, Avraham Ofir (Old Testament essays, 2016)
This study discusses three major explanations by medieval biblical commentators for Moses's meeting with Pharaoh by the Nile in the early morning hours prior to the plagues of blood and wild beasts. The exegetical principle underlying these interpretations is the view that some royal practices were shared by rulers of ancient Egypt and by medieval Muslim and Christian European rulers. Ibn Ezra claimed that Pharaoh ventured out to check the level of the water, as customary of Muslim sultans in his own time. Ibn Caspi suggests that Moses was asked to meet Pharaoh by the Nile where he was accustomed to holding a ball game with his escorts. It seems that he refers to a game of polo that was very popular among Mamluk kings. Bechor Shor and Hizkuni claimed that Pharaoh would get up early to go hunting using birds of prey. Hunting with birds was a common professional sport among the nobility in medieval times. French commentators used the life style of European nobility and royalty in medieval times to reach conclusions about ancient Egypt.